Daredevils 21 stories of extraordinary daring : with exercises for developing reading comprehension and critical thinking skills - Billings, Henry (Critical reading series, 1999)
Nonfiction articles profiling adventurers, sports heroes and stuntmen. Each is followed by reading comprehension and critical thinking exercises.